(untitled) (Research, Society and Development, 2022)
The study by objective describes the results of the quality studies. The leaves were dried and pulverized, and the powders were selected for pharmacognostic tests for pH, foam index, moisture determination and density. From maceration of maceration with ethanol, the extract of the leaves obtained (E) and through the fractions of maceration, dichlorom of half hexanol, followed by prospection phytoethanolic by half-ethane and chemical reflux methane by reflux. For in silico studies, Luteolin 7-[βglucopyranosyl]-(1→2)-βramnosyl-(1→6)β-glucopyranoside, Luteolin-7-O Rutinoside, β-Sitosterol, Campesterol, Friedelinol , lupeol, justiflorinol and apigenin the programs Marvin JS, PreADMETox and OSIRIS were used to evaluate the toxicological aspects of the species associated with the in vitro test against Artemia Salina L. of humidity within the parameters recommendations, with low density and neutral pH. In phytochemical analysis, flavonoids, coumarins, terpenes and steroids, tannins and depsones were detected. Among the non-genic genetics, β -S-Campesterol, Friedelinolforam, apigenin and luteolin7-O-carcinoside are not carcinogens. The EEF and the fractions showed levels of toxicity against the Artemia salina test.